Jared Naranjo: capstone - Naranjo, Jared, artist (Colorado State University. Libraries, 2014)
The artist's statement: Art means control. Control gives you many options. Color, scale, position, space; they all become dependent. Then there are reactions. These complicate the decisions made. A give and take ensues, and this is where I find art and myself. I enjoy the frivolity of instantaneous marks; non-prescribed and subconscious. Then, rational envelops, demanding reason and clarity. The balance to find energy and order becomes enthralling. Bracing for the impact of intuition into fundamentals connects me to institution and enlightenment. Order becomes temporal, contextual. Creativity activates imagination and consequence. This control, or reaction to the lack of, is what inspires me to create art.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.